Измерение импульсных магнитных полей - Шаламов, С. П. (НТУ "ХПИ", 2014)
Проведен обзор методов измерения импульсных магнитных полей (ИМП). Описаны принципы действия датчиков ИМП на основе эффектов Холла, Фарадея, магнитосопротивления, а также метод с использованием феррозонда Разъяснены особенности применения датчиков ИМП, приведены их преимущества и недостатки. Также рассмотрен метод на основе электромагнитной индукции. Разъяснен принцип конструирования датчика.

A review of methods for measuring pulsed magnetic fields (PMF) is held. The principles of operation of the PMF sensors are described on the basis of Hall’s and Faraday’s effects, magnetoresistance and terrasond. The features of using PMF are explained, their advantages and disadvantages are shown. A method based on electromagnetic induction is also discussed. The concept of designing the sensor is explained.
Measurement of pulsed magnetic fields
Keywords: эффект Холла; эффект Фарадея; эффект магнитосопротивления; феррозонд; электромагнитная индукция; Hall’s effect; Faraday’s effect; magnetoresistance effect; terrasond; electromagnetic induction